Schneiderian Membrane Collateral Damage Caused by Collagenated and Non-Collagenated Xenografts: A Histological Study in Rabbits - Yasushi Nakajima; Daniele Botticelli; Ermenegildo Federico De Rossi; Vitor Ferreira Balan; Eduardo Pires Godoy; Erick Ricardo Silva; Samuel Porfirio Xavier (MDPI AG, 2023)
Background: The Schneiderian membrane (SM) that is in contact with biomaterial granules may become thinner and eventually perforate. It has been shown that these events are related to the biomaterial used. Hence, the main aim of the present study was to compare the damaging effects of two xenografts with different resorbability rates on SM. The secondary aim was to evaluate the possible protection from damage offered by a collagen membrane placed adjacent to the SM and by inward displacement of the bone window with the SM during elevation. Methods: Thirty-six albino New Zealand rabbits underwent bilateral sinus elevation. One group of 18 animals received deproteinized bovine bone mineral (DBBM group) and the other received swine-collagenated corticocancellous bone (collagenated group). Moreover, in the DBBM group, the bone window was displaced inward during elevation in one sinus together with the SM. In the collagenated group, a collagen membrane was placed adjacent to the SM in one sinus. Six animals were assessed per period after 2, 4, and 8 weeks. Results: The mean pristine mucosa width ranged between 67 µm and 113 µm, and none had a width of <40 µm. In the 2-week group, the elevated mucosa of the DBBM group presented 59 thinned sites and five perforations, while in the collagenated group, 14 thinned sites and one perforation were observed. Damage to SM decreased in number in the 4-week treatment group. In the 8-week group, the number of thinned sites in the DBBM group increased to 124, and the perforations to 8. In the collagenated group, 7 thinned sites and 1 small perforation were observed. Conclusions: More damage to the Schneiderian membrane was observed in the DBBM group than in the collagenated group. The presence of the inward bone window offered protection from damage to the Schneiderian membrane.